Розробка компонентів інформаційно-облікової системи мережі пунктів прийому вторинної сировини - Чередніков, М. В. (ХНУРЕ, 2024)
A crucial component of the information accounting system is the database management system (DBMS). This system is responsible for storing, organizing, and accessing data used within the information system framework. The selection of a suitable DBMS is a critical task as it directly impacts the efficiency and productivity of the system as a whole. A properly chosen DBMS can ensure fast data access, efficient storage, and optimized query processing. Conversely, an incorrect choice of DBMS can lead to productivity issues, low system performance, and difficulties in maintenance and development.
Keywords: інформаційно-облікова система; вторинна сировина